Elderly Abuse and Its Associated Factors in Chandragiri Municipality: A Cross-Sectional Study (One Health Journal of Nepal, 2024)
Introduction: Elder abuse is a complex issue that affects older people as a result of poor physical and mental health, aging, shared living, social isolation, a lack of support, and a generation gap. It is the result of shifting socioeconomic paradigms and demographic developments, which have an impact on individuals, families, and societies. The main aim of this study was to determine the prevalence of elder abuse and the factors that are linked to it among the elderly population in the Chandragiri municipality.Methods: This was a cross-sectional study conducted among 204 elderly people over 60 years residing in a community of Chandragiri municipality through face-to-face interviews using a structured questionnaire. Simple random sampling was used to select wards and proportionate stratified sampling was used to select participants from each ward. Descriptive and bi-variate analysis was done using SPSS v.25.Results: More than two-thirds (67.6%) of the elderly experienced at least one form of abuse. Caregiver neglect (57.8%) and psychological abuse (42.2%) were the most common types of abuse. This study showed that 17.6% of the elderly experienced sexual abuse. Elderly abuse was strongly associated with illiteracy (p value=0.032) and Cancer (p value= 0.027).Conclusions: The majority of the elderly had been abused in some way, the most common being caregiver neglect, followed by psychological abuse. A deeper investigation is required to learn more about the true nature of elderly abuse in Nepal and appropriate strategies should be adopted for healthy aging without any sort of abuse against them.